2008
DOI: 10.1136/jmg.2008.062232
|View full text |Cite
|
Sign up to set email alerts
|

Risk reducing mastectomy: outcomes in 10 European centres

Abstract: We conclude that risk reducing surgery is highly effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 28 publications
0
45
0
2
Order By: Relevance
“…However, the sample size was small. Therefore, further studies are required to confirm these numbers [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the sample size was small. Therefore, further studies are required to confirm these numbers [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…They are advised that undertaking this procedure before 50 y of age will also reduce their risk of breast cancer and that this risk reduction is not substantially abrogated by taking hormone replacement therapy (6).…”
Section: Methodsmentioning
confidence: 99%
“…Many women with BRCA1 or BRCA2 mutations now seriously consider undergoing bilateral risk-reducing mastectomy (BRRM) and/or bilateral risk-reducing salpingo-oophorectomy (BRRSPO). The efficacy of surgical procedures for reducing the risk of breast and ovarian cancer is now beyond dispute (2)(3)(4)(5)(6). However, uptake rates vary enormously with a much lower uptake in Israel and southern Europe compared with northern Europe (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…While ovarian screening in high-risk groups is not effective, breast cancer screening is indicated and there is evidence of increased sensitivity of magnetic resonance imaging (MRI) for detecting malignancies in younger BRCA carriers [8,9], compared to mammography. Risk-reducing mastectomy (RRM) and/or oophorectomy (RRSO) results in a significant decrease in mortality in high-risk women [6,7,10,11]. Domcheck et al [11] found that RRSO was associated with lower all-cause mortality, as well as lower breast cancerspecific and ovarian cancer-specific mortality.…”
Section: Introductionmentioning
confidence: 99%